Tourniquet application during TKA did not affect the accuracy of implant positioning: a randomized clinical trial - Stetzelberger, Vera; Obertacke, Udo; Jawhar, Ahmed (Knee surgery, sports traumatology, arthroscopy, 2018)
PurposeThe accuracy of the identification of anatomical landmarks with versus without tourniquet application and its effect on implant positioning remained unknown. Therefore, the hypothesis of the present study was that tourniquet application did not affect the accuracy of the reconstruction of the mechanical leg alignment, the joint line level, and the patellar height.MethodsThe prospective randomized monocentric trial (Clinical-Trials.gov NCT02475603) included a total of 86 patients scheduled to undergo primary TKA. The patients were allocated to receive TKA with (Group A, n = 43) or without tourniquet (Group B, n = 43). The mechanical leg alignment, the joint line level (modified Kawamura), and the patellar height (Plateau-patella angle, Insall Salvati index, and modified Insall Salvati index) were measured pre- and postoperatively on standardized calibrated digital radiographs. Mean, SEM, median, range, and p value were calculated for each parameter.ResultsThere was no statistical difference between the groups with regard to demographics, preoperative deformity, implant design, and surgical technique (n.s.). The mechanical leg alignment, the joint line level, and the patellar height revealed, in both groups, similar results pre- and postoperatively (n.s.).ConclusionThe mechanical leg alignment, the joint line level, and the patellar height could be accurately reconstructed with and without tourniquet use. With respect to clinically relevant surrogate parameters of implant positioning, TKA can safely be performed without a tourniquet. Available data do not support a routine use of tourniquet during TKA and might justify a change of the clinical pathway.Level of evidenceLevel I.